INTERACTION BETWEEN DIETARY MINERAL AND PHYTASE ON BIOLOGICAL PERFORMANCES OF JAPANESE FLOUNDER, Paralichthys olivaceus. PART I. GROWTH, FEED INTAKE, AND WHOLE BODY MINERAL CONTENT - Asda Laining; Lidemen Lidemen; Manabu Ishikawa (Indonesian Aquaculture Journal, 2013)
In order to determine the effect of dietary calcium (Ca), inorganic phosphorus (IP), and phytase (P) supplementation in marine fish, a 2 x 2 x 2 factorial design was arranged to observe the interrelationship between dietary Ca and IP with the presence of dietary phytase. Two levels of dietary Ca at 0% and 0.2% combined with either 0% or 0.25% of dietary IP and either with 0 and 2,000 FTU phytase/kg diet, respectively to formulate eight experimental diets. SPI-based diet was used as basal diet and the sources of Ca, IP, and phytase were similar to those used in the previous experiment. Juvenile Japanese flounder with initial body weight around 0.6 g was fed the test diets. After 30 days of feeding trial, the results showed that both dietary IP and phytase, but not dietary Ca significantly enhanced the growth and feed intake. The highest growth was achieved in fish fed a diet containing the Ca, IP, and phytase supplement among groups. Fish fed diet without the three dietary supplements had the lowest SGR and did not significantly improve by supplementing dietary Ca. Feed intake (FI) and was significantly influenced by dietary IP and phytase, not dietary Ca while feed conversion ratio (FCR) was significantly affected by all dietary treatments. Interaction effect was detected between dietary Ca and IP, between dietary IP and P on FCR. Total phosphorus content in whole body was significantly increased by supplementing all dietary treatments which was highest in fish fed 0.25 IP/0.2 Ca/P. Significant interaction was observed between dietary IP and P on this parameter. Whole body Ca content was significantly improved by either dietary IP or Ca and not dietary P. As conclusion even without inorganic Ca supplement, dietary IP at level of 0.25% or 2,000 FTU phytase/kg diet could enhance growth and FI of fish as well as whole body phosphorus content of juvenile Japanese flounder when diet basal contained organic Ca around 1.2%.